Length-weight relationship and condition factor of wild, grow-out and 'loose-shell affected' giant tiger shrimp, Penaeus monodon (Fabricius, 1798) (Decapoda: Penaeidae) - Gopalakrishnan, Ayyaru Navaneetha; Rajkumar, Mani; Rahman, Mohammad Mustafizur; Sun, Jun; Antony, P.J.; Venmathi Maran, Balu Alagar; Trillès, Jean Paul (John Wiley & Sons, Inc, 2014)
Length-weight relationships and condition factors of wild, cultured, and cultured loose-shell affected Penaeus monodon (2,609 specimens total) were studied from March to August 2007. The regression equation for healthy cultured shrimps was log W = -1.811 + 2.721 log L (r2 = 0.71); log W = -1.444 + 2.485 log L (r2 = 0.91) for wild shrimps; and log W = -1.112 + 2.237 log L (r2 = 0.92) for loose-shell affected shrimps. All shrimps showed negative allometric growth, although ancova indicated significant differences (P < 0.05) among them. This study presents the first known reference dealing with LWRs and condition factors of cultured, wild and loose-shell affected P. monodon